A Cooperative Shared Control Scheme Based on Intention Recognition for Flexible Assembly Manufacturing - Zhou, Guangbing; Luo, Jing; Xu, Shugong; Zhang, Shunqing (Frontiers in Neurorobotics, 2022)
Human–robot collaboration (HRC) has been widely utilized in industrial manufacturing and requires a human to cooperate with a robot at the same workspace. However, as HRC focuses on workspace sharing along with independent work, it is not a real collaboration between a human and a robot and, thus, cannot guarantee a smooth cooperation and synchronous operation. To this end, a cooperative shared control scheme based on intention recognition is proposed in this study by sharing workspace and time. In the proposed method, a classification algorithm based on 3D point cloud is utilized to recognize the human operation intention. Then, the robot can select a suitable tool to match the human’s operation. A robot motion control algorithm is developed to detect the obstacles in the HRC process. A cooperative control strategy is introduced to achieve synchronous operation. A simple assembly task is also performed to demonstrate the proposed scheme’s effectiveness. The proposed HRC method with shared control can be extended to more complicated and delicate flexible tasks in assembly manufacturing.